Clinicoprognostic and Histopathological Features of Guttate and Plaque Psoriasis Based on PD-1 Expression - Chang-Jin Jung (MDPI AG, 2021)
Several studies have determined the correlation between programmed cell death protein-1 (PD-1) and chronic plaque psoriasis (CPP). However, limited studies have assessed the association between PD-1 expression and the clinicoprognostic and distinct clinicopathological characteristics of CPP and guttate psoriasis (GP). Twenty-nine patients with skin biopsy-confirmed CPP were recruited at the Asan Medical Center between January 2018 and June 2020, and 33 patients with biopsy-confirmed GP were enrolled between January 2002 and June 2020. The clinicoprognostic and histopathological characteristics were analyzed according to immunohistochemical PD-1 expression in the epidermal or dermal inflammatory infiltrates. The CPP and GP lesions were divided into PD-1-low and PD-1-high groups. The CPP epidermal PD-1-high group had typical histopathological changes and significantly higher psoriasis area and severity index scores (p = 0.014) and disease duration (p = 0.009) than the epidermal PD-1-low group. In patients with GP, compared with the dermal PD-1-high group, the dermal PD-1-low group exhibited significantly higher disease duration (p = 0.002) and relapse rate of plaque psoriasis (p = 0.005) and significantly lower relapse-free survival (p = 0.016). Upregulated epidermal PD-1 expression was correlated with the chronicity and severity of CPP, while downregulated dermal PD-1 expression was correlated with poor prognosis of GP.